Past, present and future epidemiology of echinococcosis in China based on nationwide surveillance data 2004–2022 - Wang, Xu; Kui, Yan; Xue, Chui-Zhao; Wang, Qian; Zheng, Can-Jun; Zhao, Jiang-Shan; Yang, Ya-Ming; Jiang, Xiao-Feng; Gong-Sang, Qu-Zhen; Ma, Xiao; Feng, Yu; Wu, Xiang-Lin; et al. (The Journal of infection, 2025)
We evaluated the epidemiological characteristics of echinococcosis, a global public health threat, in China to inform global control efforts. Descriptive, statistical, cluster, spatial, and trend analyses were used to evaluate the epidemiology at national, provincial, and county levels based on 2004–2022 nationwide surveillance data from China. Between 2004 and 2022, China recorded 72,676 cystic echinococcosis (CE) cases, 11,465 alveolar echinococcosis (AE) cases, and 5703 others, with an average annual cases per million (ANpM) of 3.45. Females had a higher incidence (ANpM = 3.87) than males (3.05), with most cases (41.15%) in the 30–49 age group, mainly among herders (38.76%) and farmers (37.82%). Seven provinces (Xizang, Qinghai, Xinjiang, Ningxia, Gansu, Sichuan, and Inner Mongolia) accounted for 98.12% of cases, with the Tibetan Plateau showing the highest rates (ANpMs = 155.51 for CE, 46.95 for AE). Surgery and case fatality rates were 39.45% and 5.23% in key surveillance regions (KSRs). Prevalence among residents (0.20%), livestock (1.33%), rodents (1.30%), and dogs (1.26%) declined with increased control funding in KSRs. Between 2023 and 2030, there will be an estimated 20,096 new cases and 45,323 cases requiring treatment. The prevalence of echinococcosis has been alleviated in China, but significant control challenges remain, requiring sustained and targeted control measures. [Display omitted] •A total of 89,844 cases in China (2004–2022), with a 3.45/1,000,000 annual incidence.•Prevalence is higher among groups of females, ages 30–49, and farmers/herders.•KSRs show a 4.05/1,000,000 mortality rate per year and a 5.23% case fatality rate.•The Tibetan Plateau has the highest annual incidence for both CE and AE.•There will be an estimated 20,096 new echinococcosis cases in 2023–2030.